The role of socio-demographics profile and Work-life conflict on life satisfaction among Working-class women in Sabah, Malaysia - Elpidia Juli; Md Sayed Uddin; Trixie Marjorie Tangit (Human Resource Management Academic Research Society (HRMARS), 2024)
Background: Life satisfaction among working-class women in Malaysia are influenced by several factors includes their socio-demographics such as marital status, age, religiosity, ethnicity and their education background. This is also not limited to other external influential factors such as work-life conflict. Only little amount of research focuses on life satisfaction among working-class women in the state of Sabah, Malaysia, in relation with their sociodemographics and work-life conflict. Objectives: Firstly, this research aims to investigate the relationship between socio-demographics and life satisfaction among working-class women in Sabah, Malaysia. Next, will also to examine the relationship between work-life conflict and life satisfaction among working-class women in Sabah, Malaysia. Methodology: A total of 348 female government servants in Kota Kinabalu, Sabah, Malaysia participated in the study by using snowball sampling method. An online questionnaire and physical questionnaires distributed to the respondents at government sectors. Results: It was shown that marital status among working-class women in government sectors partially mediated the relationship between dimensions in work-life conflict and dimensions in life satisfaction. Morever, there was a correlation between all dimensions in work-life conflict and cognitive life satisfaction (p < 0.01) among working-class women in government sectors. Based on results, female government servants in Kota Kinabalu, Sabah, Malaysia’s level of life satisfaction are partially influenced by their marital status, especially married individuals. Further research is needed to investigate whether the role of female government servants’ grade position in their work organizations influence their level of life satisfaction.